How do speed and security influence consumers' payment behavior? - Scott Schuh; Joanna Stavins (European Central Bank (ECB), 2015)
The Federal Reserve named improvements in the speed and security of the payment system as two of its policy initiatives for 2012–2016. Using new data from the 2013 Survey of Consumer Payment Choice (SCPC) and models from earlier research, we estimate how various aspects of speed and security influence consumers' decisions to adopt and use payment instruments. Some aspects of speed and security have a statistically significant influence on the adoption and use of selected payment instruments, but not as much as other characteristics of payment instruments. Using econometric models to simulate selected policies proposed by the Fed, we show that faster speed of payment deduction for Automatic Clearing House (ACH) transactions would slightly increase consumers' adoption of ACH-based payment methods, while enhanced security of payment cards would marginally increase the use of credit and debit cards. However, neither improvement is likely to increase consumer welfare much because consumer demand for payments is very inelastic with respect to speed and security. Our analysis focuses exclusively on consumers' behavior and does not include potential benefits of improvements to the payment system that would directly benefit businesses or financial institutions. In addition, preventing security breaches may preserve public confidence in the payment system, benefitting consumers even if they do not change their payment behavior.
Keywords: D12; D14; E58; 330; Central Banking; Consumer Economics; Empirical Analysis; Household Saving; payment system; Personal Finance